SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI GURU SMA DI SMA IT CORDOVA 3 TANGERANG - Hanafiah; Ratnawulan, Teti; Khaqiqi, Irfan Qomarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide an in-depth description of the academic supervision process carried out by the principal in an effort to improve teacher competence at SMA IT Cordova 3 Tangerang. Using a qualitative approach with a case study method, this research highlights four main aspects of academic supervision: planning, implementation, evaluation, and follow-up. Data were collected through interviews, observations, and document analysis, and were thematically analyzed using triangulation techniques. The results of the study show that the supervision planning was systematically designed and oriented toward teachers’ needs, although there were still challenges in explicitly integrating spiritual aspects and the integrated Islamic context. The implementation of supervision reflected a reflective and dialogical approach, although it has not been fully optimized in the use of technology and differentiation of approaches based on teachers’ characteristics. Evaluation was conducted participatively, but has not yet fully impacted practice changes due to limitations in systematic reflection and follow-up. The follow-up of supervision, although not yet fully structured, has begun to be directed toward community-based professional development strategies and the individual needs of teachers. This study concludes that the effectiveness of academic supervision is greatly influenced by the principal’s leadership quality as a learning facilitator and professional coach. These findings are expected to serve as a reference in developing a contextual, humanistic, and transformative model of academic supervision in integrated Islamic schools. Keywords: Academic supervision, teacher competence, principal, professional development, integrated Islamic school, secondary education.